(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Malassezia spp. is a lipid-dependent yeast that their excessive presence and proliferation on the skin can be associated with several dermatological conditions such as pityriasis versicolor, dandruff, atopic dermatitis, seborrheic dermatitis, etc. Environmental factors and human habits can influence the development of Malassezia spp. on the skin and cause diseases. Objectives: To survey the prevalence of Malassezia spp. infection in dermatological patients visiting the Ho Chi Minh City Dermatology Hospital and related factors. Methods: A cross-sectional descriptive analysis was conducted from April to May 2024 at the Ho Chi Minh City Dermatology Hospital and the Department of Laboratory Medicine, University of Medicine and Pharmacy, Ho Chi Minh City. Samples were observed fresh, cultured, and identified. Results: 24 out of 123 patients (19.5%) were found to be infected with Malassezia spp. via fresh observation. There were 38 (30.09%) cases of positive culture growth, with the species distribution as follows: Malassezia furfur 12 (31.6%), Malassezia globosa 10 (26.3%), Malassezia pachydermatis 8 (21.1%), Malassezia restricta 6 (15.8%), Malassezia sympodialis 1 (2.6%), and other Malassezia spp. 1 (2.6%). The age group 30-45 had the highest rate at 9/24 (37.5%), and males were more affected than females 17/24 (70.8%) with p=0.173*. The most common lesion sites were the back, chest, and abdomen 18/24 (75%), with skin discoloration symptoms observed in 24/24 (100%) patients. Conclusion: The infection rate of Malassezia spp. in dermatological patients was 19.5%, with a culture isolation rate of 30.09%, identifying 5 Malassezia spp.: Malassezia furfur (31.6%), Malassezia globosa (26.3%), Malassezia pachydermatis (21.1%), Malassezia restricta (15.8%), Malassezia sympodialis and Malassezia yamatoensis (2.6%). Related factors include the most common lesion sites being the back, chest, and abdomen, and the presence of skin discoloration symptoms.